Karnataka scheduled castes and scheduled tribes (prohibition of transfer of certain lands) act, 1978: Karnataka act no. 2 of 1979 - Narayana, P.S. ed. and Puliani, Yashpal ed. (Bangalore Karnataka law journal publications, 2023)
Karnataka act, as amended by Karnataka act no. 30 of 2023
Keywords: Karnataka act